Researcher-implementer partnerships for learning and impact: Lessons from IFPRI's experiences with nutrition-sensitive programming - Bliznashka, Lilia; Sproule, Katie (International Food Policy Research Institute, 2022)
Researcher–implementer partnerships are a subject of growing interest in CGIAR, and beyond, to help ensure research is relevant, cost-effective, and likely to scale up quickly among potential users. In 2021, as part of its synthesis strategy, the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) commissioned an external review of the International Food Policy Research Institute’s (IFPRI) researcher–implementer partnerships in the context of nutrition-sensitive programming.1 The objective of this external review was to characterize and evaluate IFPRI’s researcher–implementer partnerships with Helen Keller International (HKI) and the World Food Programme (WFP). In the context of this external review, “research–implementer partnership” referred to long-term partnerships between two organizations that lasted beyond the life of a single project or funding stream. This review aimed to characterize and document how researcher–implementer partnerships work, what factors facilitate or constrain these types of partnerships, and how the evidence generated by them influences changes in programs and policies at the partner organizations and beyond. The study was completed through a desk review of peer-reviewed and gray literature and a series of in-depth interviews with key informants from IFPRI, HKI, WFP, and staff from other implementing organizations, funding organizations, and academic institutions. In total, 15 individuals from 8 organizations were interviewed virtually in July and August 2021. Data were analyzed using thematic content analysis. This brief synthesizes the lessons learned about effective researcher–implementer partnerships and the implications for researchers, implementers, and funders.